rFIP-nha activates macrophages towards a pro-inflammatory phenotype via AIM2 inflammasome modulation - Liu, Yusi; Li, Zhen; Wichers, Harry; Bastiaan-Net, Shanna; Hoppenbrouwers, Tamara (Frontiers in Cell and Developmental Biology, 2025)
Fungal immunomodulatory proteins (FIPs) are small proteins from fungi with considerable immunomodulatory activity. FIP-nha (Nectria haematococca) contains two glycosylation sites at positions N5 and N39, and displays a high thermostability and notable anti-tumour activity. However, FIP-nha’s immunomodulatory activity on macrophages and the associated mechanism remain unclear. In this study, three rFIP-nha glycan mutants (N5A, N39A, N5+39A) were recombinantly expressed in Pichia pastoris. To test the impact on FIP-nha’s immunomodulatory activity, the phagocytotic activity, cytokine secretion, and gene expression of THP-1 macrophages were investigated. rFIP-nha and its mutants reduced macrophage phagocytosis, and induced IL-1β, IL-12 and IL-10 cytokine secretion significantly, indicating that the protein confers a pro-inflammatory behaviour on THP-1 macrophages. However, there were no obvious differences among the different glycan mutants, indicating that the observed activation mechanisms are likely glycosylation-independent. Furthermore, to study the immunomodulatory mechanism, four kinds of inflammasomes (NLRP1, NLRP3, NLRC4 and AIM2) were tested at transcriptional level. AIM2 was found to be 10-fold upregulated. Then, THP1-KO-ASC cells and AIM2 related inhibitors showed that IL-1β release induced by rFIP-nha is ASC signalling pathway dependent. Taken together, these findings suggest that rFIP-nha activates THP-1 macrophages in a pro-inflammatory way by activating the AIM2 inflammasome.